Pseudodominant Alport syndrome caused by pathogenic homozygous and compound heterozygous COL4A3 splicing variants. (9th December 2021) - Mohamed, Maha; Tellez, James; Bergmann, Carsten; Gale, Daniel P.; Sayer, John A.; Olinger, Eric
Abstract: Alport syndrome is a genetic disorder affecting the basement membranes of the kidney, ear and eye, and represents a leading cause of monogenic kidney disease. Alport syndrome is genetically heterogeneous with three key genes involved ( COL4A3‐5 ) and several transmission patterns, including monogenic X‐linked, autosomal recessive/dominant and digenic. We report a consanguineous family where 13 individuals presented variable features of Alport syndrome including kidney failure on two generations and male‐to‐male transmission, suggesting autosomal dominant inheritance. COL4A3‐5 gene panel analysis surprisingly reveals two distinct, confirmed splice‐altering variants in COL4A3 (NM_000091.4: c.1150+5G>A and c.4028‐3C>T) present in homozygous or compound heterozygous state in individuals with kidney failure. This adds a further mode of transmission for Alport syndrome where, in a consanguineous family, the independent segregation of two variants at the same locus may create a pseudodominant transmission pattern. These findings highlight the importance of a molecular diagnosis in Alport syndrome for genetic risk counselling, given the variable modes of inheritance, but also the pitfalls of assuming identity by descent in consanguineous families.